Productivity Performance of Sheep in Silvopastoral Systems With Cashew Tree Compared to Grass Monoculture - Santos, Maurilio Sousa dos; Oliveira, Maria Elizabete de; Leal, Tânia Maria; Rodrigues, Marcônio Martins; Alves, Arnaud Azevedo; Carvalho, Wanderson Fiares de; Abdalla, Adibe Luis; Moreira, Marcelo Zacharias (Journal of Agricultural Studies, 2022)
The goal in this study was to evaluate the production of sheep and forage silvopastoral systems (SPSs) with cashew trees, compared to the production on grass monoculture. The treatments consisted of three grazing systems: one Massai grass monoculture (Panicum maximum cv Massai) (MONO), and two SPSs: intercrop of Massai grass + cashew tree (Anacardium occidentale) (SM) and intercrop of grass- Massai grass + Estilosantes Campo Grande (Stylosanthes capitata × S. macrocephala) + cashew tree (SME), in a completely randomized split plot design with four replications. The photosynthetically active radiation varied from 45 to 59% in SPSs, the presence of cashew trees created a microenvironment with lower temperatures and higher relative humidity throughout the day. Forage mass in the monoculture and in the SPSs was on average 2,116.65 kg dry matter (DM). ha-1; the participation of the legume in the forage mass was 44%. Greater stocking rate was found in the monoculture, however the gain per area was higher in the SME. In the SPSs, crude protein content of the grass increased by 46.2%, and there was a higher forage intake and weight gain of sheep, mainly in the system with legume. The silvopastoral system with cashew trees, Massai grass, estilosantes and sheep is feasible to optimize land use, with better gain per animal and area in relation to grass monoculture.